2009
DOI: 10.1103/physreve.80.061904
|View full text |Cite
|
Sign up to set email alerts
|

Base-pair opening and bubble transport in a DNA double helix induced by a protein molecule in a viscous medium

Abstract: The protein-DNA interaction dynamics is studied by modeling the DNA bases as classical spins in a coupled spin system, which are bosonized and coupled to thermal phonons and longitudinal motion of the protein molecule in the nonviscous limit. The nonlinear dynamics of this protein-DNA complex molecular system is governed by the completely integrable nonlinear Schrödinger (NLS) equation which admits N -soliton solutions. The soliton excitations of the DNA bases in the two strands make localized base-pair openin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 66 publications
1
32
0
Order By: Relevance
“…However, Sataric and Tuszinsky 9 used the Peyrard-Bishop model 10 and found that the interaction between the DNA and the proteins generates breather solitons spontaneously. Recently, Vasumathi and Daniel 11 proposed a theoretical model based on the spinlike model, and confirmed that bubbles that are experimentally observed within the process of base-pair opening are simply due to the presence of proteins around the DNA molecule. The purpose of the present work is to update this model by taking into account the helicoidal coupling, as introduced by Tabi et al, 7 in order to model the DNAprotein interaction in a more realistic way.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, Sataric and Tuszinsky 9 used the Peyrard-Bishop model 10 and found that the interaction between the DNA and the proteins generates breather solitons spontaneously. Recently, Vasumathi and Daniel 11 proposed a theoretical model based on the spinlike model, and confirmed that bubbles that are experimentally observed within the process of base-pair opening are simply due to the presence of proteins around the DNA molecule. The purpose of the present work is to update this model by taking into account the helicoidal coupling, as introduced by Tabi et al, 7 in order to model the DNAprotein interaction in a more realistic way.…”
Section: Introductionmentioning
confidence: 70%
“…2 + 2 −Jf a n a + n+1 + a + n a n+1 − a + n a n − a + n+1 a n +b n b + n+1 + b + n b n+1 − b + n b n − b + n+1 b n −Jg a n b + n+h + a + n b n+h + b n a + n+h + b + n a n+h −a + n+h a n+h − b + n+h b n+h − a + n a n − b + n b n − − 1 X n+1 − X n−1 a n b + n + a + n b n − a + n a n −b + n b n − 2 y n+1 − y n−1 a + n a n + b + n b n (11) Delivered by Ingenta to: Chinese University of Hong From the above semi-classical Hamiltonian it is easier to construct the equations of motion as i a n t = a n H = F 1 a n a + n a n+1 a + n+1 a n+h a + n+h (12a)…”
Section: Model and Dynamical Equationsmentioning
confidence: 99%
“…4(b) and 6. It may be interesting to point out that this approach can be used to study modulation instability in DNA double helix [30] as well as DNA-protein interaction [31].…”
Section: Nonlinear Models Of Dnamentioning
confidence: 99%
“…Surprisingly, the passage of the DNA kinks through the CDS region was not modeled by investigators, though the necessary mathematical formalism has been already developed. We can point out the model of Peyrard and Bishop [10] that takes into account the transverse motions of nucleotides, the Y-model [11][12][13] that takes into account the angular displacements of nitrous bases, the combined model [14] that takes into account both the angular and the transverse displacements, and numerous modifications of these models [15][16][17][18][19][20]. Any of them could be used for the purpose.…”
Section: Introductionmentioning
confidence: 99%